Rancang Bangun Peralatan Pengukur Kuat Sinyal Seluler untuk Modul Praktikum Lab Telkom Wireless - Anggita Sukma Nur Anggraini; Aisah Aisah; Abdul Rasyid (Politeknik Negeri Malang, 2021)
This study was designed to facilitate data retrieval in order to monitor at any time via a smartphone with RSSI, RSRP, and RSRQ parameters. In this study, the test method was carried out on a predetermined route by comparing the measurement results on the measuring instrument and the G-Nettrack Pro. Data is taken at rest at 20 points, test drives with an average speed of 10 km/hour, and 20 km / hour using Telkomsel and Indosat providers. The RSSI measurement parameter for the Telkomsel provider has an average of -66.3 dBm on the G-Nettrack Pro software and on the measuring instrument the average value is -58.6 dBm. While the Indosat provider has an average value of -75.5 dBm on the G-Nettrack Pro software and on the measuring instrument the average value is -59.7 dBm. The RSRP measurement parameter for the Telkomsel provider has an average of -83.05 dBm on the G-Nettrack Pro software and on the measuring instrument the average value is -87.26 dBm. While the provider Indosat has an average value of -92.7 dBm on the G-Nettrack Pro software and on the measuring instrument the average value is -90.3 dBm. The RSRQ measurement parameter for the Telkomsel provider has an average of -7.73 dB on the G-Nettrack Pro software and on the measuring instrument the average value is -10.8 dB. While the Indosat provider has an average value of -12.89 dB on the G-Nettrack Pro software and on the measuring instrument the average value is -10.8 dB